'Organization Science': A new prospective to assess marine protected areas effectiveness. (November 2015) - Scianna, Claudia; Niccolini, Federico; Gaines, Steven D.; Guidetti, Paolo
Abstract: Marine Protected Areas (MPAs) are widely considered as useful tools to achieve both conservation and resource management goals. They have the potential to produce a wide array of positive socio-ecological effects. Their effectiveness, however, varies dramatically. The sources of this variability are numerous and, in some cases, quite well studied. Yet, a significant portion of the variability in MPAs effectiveness still remains unexplained. MPAs, due to a number of intrinsic features, can be considered "organizational systems", a definition recognizing the fact that 1) their effectiveness can be influenced by their own organizational dimensions and 2) they could be analyzed employing the typical tools provided by 'Organization Science' (hereafter OS). Here we analyze the available literature on MPAs on a worldwide scale to explore whether and how the principles of OS have been used as a scientific basis for the evaluation of MPA effectiveness. We found that no study explicitly used a comprehensive OS framework for evaluating effectiveness in the context of MPAs. Just 20 studies considered some organizational dimensions in their analysis (e.g. professionalism of the organization members, vision, goals, strategy and networking), but not in a comprehensive manner. The outputs of our review stress the limited use of the OS methodologies and principles in the context of MPAs so far. We posit that there is a significant potential for new insights in MPA science thanks to a more integrated implementation of an OS framework for the interpretation and improvement of MPA socio-ecological effectiveness. Highlights: We reviewed available literature on MPAs and Organization Science (OS). Overall, no studies comprehensively used OS to assess MPAs effectiveness. Only 20 publications did take into account few organizational dimensions. OS is a promising approach but its implementation in the context of MPAs is still limited.